Topical Anesthetic Abuse Keratopathy and Its Management - Sonmez, Baris; Beden, Umit; Ozarslan, Yakup; Erkan, Dilek (Turkish Ophthalmological Soc, 2008)
Purpose: To report a case series of topical anesthetic keratopathy and to evaluate the effectiveness of the treatment regimens in three cases. Methods: Retrospective case series. Results: Four eyes of three patients were diagnosed for topical anesthetic abuse keratopathy. The drug was proparacaine hydrochloride 0.5% at all cases with an exposure time between 10 days to three months. The mean visual acuity was 0.1. The corneal ulcers were 3.6x6.3mm to 7.5x9.0mm in size and 10 - 80% corneal thinning was present. A stromal infiltrate accompanied each corneal ulcer. Three eyes had hypopyon. One patient denied any treatment and his cornea healed with scarring. The other patient healed with minimal corneal clouding after conventional medical therapy in 14 days. The last patient required amniotic membrane transplantation for the treatment of the resistant corneal ulcer and healed successfully with final visual acuities of 0.7 and 0.8 in the right and the left eyes respectively. Conclusion: Topical anesthetic abuse can result in serious corneal complications. However, supportive medical treatment and the use of amniotic membranes may increase the chance for the treatment success.
Keywords: Topical Anesthetic Abuse; Corneal Melting; Amniotic Membrane